Selectively Stiffening Garments Enabled by Cellular Composites. Issue 9 (18th March 2022) - Kwon, Junghan; Choi, Inrak; Park, Myungsun; Moon, Jeongin; Jeong, Bomin; Pathak, Prabhat; Ahn, Jooeun; Park, Yong‐Lae
Abstract: Recent efforts on wearable robots have focused on augmenting the motor performance and/or protecting the wearer's body with lightweight structures. However, providing human‐scale force and structural stiffness usually conflicts with the wearability. Inspired by sandwich‐structured composites with high structural strengths, widely employed in both nature and man‐made structures, a mechanism of selectively stiffening garments (SSGs) utilizing anisotropic cellular cores and rubber‐laminated face sheets is proposed. While the proposed mechanism shows a high compliance allowing for conformity to the wearer's body when unjammed, it provides a significantly high force density when jammed, compared to conventional jamming methods, allowing for the ability to adjust mechanical properties based on the designs and materials. In this paper, various designs of the sandwich jamming structures for the SSGs with analytical characterizations and experimental validations are introduced. Potential applications for force and motion assistance are also demonstrated and impacted mitigation. Abstract : A mechanism of selectively stiffening garments utilizing anisotropic cellular cores and rubber‐laminated face sheets is proposed. While the proposed mechanism shows a high compliance, allowing for conformity to the wearer's body when unjammed, it provides a significantly high force density when jammed, compared to conventional jamming methods, allowing for the ability to adjust mechanical properties based on the designs and materials.